2022
DOI: 10.1126/sciadv.abn2627
|View full text |Cite
|
Sign up to set email alerts
|

Reduced platelet forces underlie impaired hemostasis in mouse models of MYH9 -related disease

Abstract: MYH9 -related disease patients with mutations in the contractile protein nonmuscle myosin heavy chain IIA display, among others, macrothrombocytopenia and a mild-to-moderate bleeding tendency. In this study, we used three mouse lines, each with one point mutation in the Myh9 gene at positions 702, 1424, or 1841, to investigate mechanisms underlying the increased bleeding risk. Agonist-induced activation of Myh9 mutant platelets was comparable to contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…From mouse models with a defect in the MYH9 gene, it has been shown that most homozygous MYH9 gene mutations are lethal and, therefore, the observed MYH9 defects are heterozygous. It has also been found that the bleeding phenotype does not necessarily depend on the extent of thrombocytopenia and may be caused by inherent defects in platelet function, such as contractility and outside-in signaling associated with integrin β3 phosphorylation and accumulation of phosphatidylinositol(3,4)P(2) following stimulation 9 , 24 . Despite numerous studies, the mechanistic relationship between the genetic defects in the MYH9 gene and the hemorrhagic phenotype of varying severity remains largely unclear, despite its practical and theoretical importance 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From mouse models with a defect in the MYH9 gene, it has been shown that most homozygous MYH9 gene mutations are lethal and, therefore, the observed MYH9 defects are heterozygous. It has also been found that the bleeding phenotype does not necessarily depend on the extent of thrombocytopenia and may be caused by inherent defects in platelet function, such as contractility and outside-in signaling associated with integrin β3 phosphorylation and accumulation of phosphatidylinositol(3,4)P(2) following stimulation 9 , 24 . Despite numerous studies, the mechanistic relationship between the genetic defects in the MYH9 gene and the hemorrhagic phenotype of varying severity remains largely unclear, despite its practical and theoretical importance 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the MYH9 gene encodes myosin IIA, which interacts with actin to form the force-generating machinery, mice with MYH9 mutations have inherently impaired contractility, determined both in vitro 24 , 27 , 28 and in vivo 9 , 24 , 29 . The impaired platelet contractility results in reduced compaction of blood clots, which is necessary for efficient hemostasis 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is supported by findings that thrombus contraction under shear depends on P 2 Y 12 and TxA 2 signaling [53], and that fibrin-induced GPVI signaling contributes to clot retraction [54]; however, tractions seem to be independent of thrombin concentration above a threshold [55]. Single platelet force might scale with spreading area [49], or more generally platelet size since murine platelets generate 25% less force in direct [56] or indirect [57 ▪▪ ,43 ▪ ] comparison to human platelets (Table 1), not excluding other inter-species differences in platelet composition or function [56].…”
Section: Mechanosensing In Thrombus Formationmentioning
confidence: 90%
“…In the present study, we examined the effects of riociguat and cinaciguat on platelet biomechanics using scanning ion conductance microscopy (SICM), a non-invasive imaging technique that allows simultaneous measurement of morphological and mechanical properties in living cells [17,18] with high resolution. SICM has already been used to investigate the Young's modulus (stiffness) of living migrating and non-migrating platelets [19] and to show that reduced platelet stiffness is related to increased bleeding in MYH9-related disease [20]. We correlated SICM measurements with F-actin and P-selectin (CD62P) immunostaining in human and wild-type (C57Bl6/J) or platelet-specific NO-GC knockout (KO) murine platelets.…”
Section: Introductionmentioning
confidence: 99%